Peranan Manajerial Kepala Sekolah, Etos Kerja Guru dan Fasilitas dalam Mengembangkan Keefektifan Pembelajaran Daring - Nina Fatimah (CV. Syntax Corporation Indonesia, 2021)
Indonesia's education system underwent a quite drastic change due to the impact of COVID 19's pandemics, learning that had been done face-to-face must turn to online learning at all levels including in primary level. In its implementation there are several important factors that must be considered, so that the online learning education system can run effectively. This research aims to find out the relationship between factors that affect the effectiveness of online learning, namely the establishment of the principal's managerial skills, the contribution of the teacher's work ethic and also the use of learning facilities carried out during the Covid 19 pandemic. To achieve this goal, this study uses a qualitatively descriptive research method with a case study approach, data collection techniques used are interviews, observation and documentation. The research was carried out at Lazuardi Cordova GIS Elementary School, with the research subjects being principals and teachers. Data obtained during the study were analyzed by data reduction steps, data presentation, and drawing conclusions. Whereas the validity test of the data is carried out by observing triangulation. The triangulation used in this study is source triangulation and technical triangulation. Based on the results of research conducted reinforcing that schools as educational institutions require synergy between various components, each component is interconnected and influences each other to achieve or increase the effectiveness of online learning in elementary school students, where the effectiveness of online learning is largely determined by the management of the principal , teacher and learning media